Sebuah Perancangan Brand Identity Industri Kecil Menengah â€œPawone Uninâ€ sebagai Identitas Usaha Katering di kota Malang - Mifthahul Haeruddin Wijaya; Pujiyanto Pujiyanto; Mahendra Wibawa (LPPM STIKI Malang, 2020)
Small and Medium Industry Pawone Unin is a catering business in the city of Malang which was founded in 2015 to offer products and services but does not yet have a business identity to be recognized by the wider community, so it is necessary to design a Small and Medium Industry Brand Identity